2018
DOI: 10.1080/01441647.2018.1552631
|View full text |Cite
|
Sign up to set email alerts
|

Urban public transport systems from new institutional economics perspective: a literature review

Abstract: The paper provides a novel perspective for the examination of urban public transport (UPT) systems based on a literature review of new institutional economics (NIE). New institutional economics is a rapidly growing interdisciplinary economic perspective which seeks to explain the role of institutions in the performance of socio-economic systems. It encompasses various economic theories including transaction cost economics, agency theory, contract theory and property rights economics. Although NIEbased approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…Organisation of public transport is also a challenge in the perspective of the new institutional economy, which strongly changes the perception of economic aspects of transport, introducing new concepts and theories such as transaction cost economics, agency theory, contract theory and property rights economics (Canitez, 2019).…”
Section: Public Transport As the Basis Of The Functioning Of Cities I...mentioning
confidence: 99%
“…Organisation of public transport is also a challenge in the perspective of the new institutional economy, which strongly changes the perception of economic aspects of transport, introducing new concepts and theories such as transaction cost economics, agency theory, contract theory and property rights economics (Canitez, 2019).…”
Section: Public Transport As the Basis Of The Functioning Of Cities I...mentioning
confidence: 99%
“…В статье [9] представлен аналитический обзор публикаций по направлению институциональной экономики ГПТ, предусматривающей изучение перевозок пассажиров транспортом общего пользования с учётом «внешнего окружения», включающего проблемы не только на уровне микроэкономики транспортных организаций, но также учёт внутригородской политики, комплекса социальных отношений, экстернальных результатов транспортной деятельности и пр . Такой подход приведёт к существенным изменениям условий, в которых станет в перспективе работать ГПТ .…”
Section: разработки в области определения обеспеченности гпт транспортными средствамиunclassified
“…In a specific way, these shortcomings are also present in the urban bus market when regulation does not exist or when it is not well applied. Different authors [5][6][7][8][9][10] have identified major failures associated with urban bus market which are next discussed.…”
Section: Market Failures In the Urban Bus Marketmentioning
confidence: 99%